Flavonoid glycosides from Olax mannii: Structure elucidation and effect on the nuclear factor kappa B pathway. (24th December 2015) - Okoye, Festus B.C.; Sawadogo, Wamtinga Richard; Sendker, Jandirk; Aly, Amal H.; Quandt, Bettina; Wray, Victor; Hensel, Andreas; Esimone, Charles O.; Debbab, Abdessamad; Diederich, Marc; Proksch, Peter
Abstract: Ethnopharmacological relevance: Olax mannii Oliv. (Olacaceae) is among the many medicinal plants used in Nigeria for the ethnomedicinal management of both cancer and inflammation. Such plants represent potential sources of innovative therapeutic agents for the treatment of cancer and other malignant disorders. While the majority of medicinal plants exert their anticancer effects by direct cytotoxicity on tumor cells, it is important that other mechanisms through which these plants can exhibit anticancer effects are investigated. Preliminary studies indicated that Olax mannii leaves are rich sources of novel flavonoid glycosides. The detailed chemistry as well the mechanisms through which these flavonoid constituents may exert their cancer chemo-preventive and therapeutic effects are, however, not yet investigated. Aim of the study: The aim of this study is to carry out a detailed chemical investigation of Olax mannii leaves and the effects of the isolated constituents on the nuclear factor kappa B (NF-κB) pathway. Materials and methods: A methanol leaf extract was subjected to various chromatographic separations to achieve isolation of flavonoid glycosides and the structures of the isolated compounds were elucidated by a combination of 1D and 2D NMR and high resolution mass spectrometry. Biological activities were assessed by measurement of cellular viability and proliferation using quantitative IncuCyte videomicroscopy, trypan blue staining and by quantification of the number of metabolically active K562 cells based on quantitation of ATP. The effect of the compounds on the inhibition of the NF-κB pathway as well as toxicity towards peripheral blood mononuclear cells to evaluate differential toxicity was also assayed. Results: Chemical investigation of the methanol leaf extract of the plant material led to the isolation of three new flavonoid triglycosides, kaempferol 3- O -[α-d -apiofuranosyl-(1→2)-α-l -arabinofuranoside]-7- O- α-l -rhamnopyranoside (1 ), kaempferol 3- O -[ β -d -glucopyranosyl-(1→2)- α -l -arabinofuranoside]-7- O- α-l -rhamnopyranoside (2 ), kaempferol 3- O -[ β -d -arabinopyranosyl-(1→4)- α -l -rhamnopyranoside]-7- O - α -l -rhamnopyranoside (3 ), in addition to fourteen known flavonoid glycosides (4-17 ). Of all the tested compounds, only compound9 (kaempferol 3-O-α-l -rhamnopyranoside) exhibited promising and specific antiproliferative activity on human K562 chronic myelogenous leukemia cells and dose-dependently inhibited NF-κB transactivation. Conclusion: The presence of this flavonoid glycoside and derivatives may account for the reported efficacy of Olax mannii leaf extract in the ethnomedicinal management of cancer and inflammation. Graphical abstract: